(untitled) (Gestión y Gerencia, 2025)
Transhumanism is an international philosophical and cultural movement that began in the mid-20th century. It focuses on improving human capacities, both physical and mental, with the aim of eliminating, among other things, physical and cognitive limitations through the use of technoscience. This essay analyzes the technological and sociocultural impact that the application of transhumanist ideals can have on societies and the role of the State in their evolutionary process. It was developed under a qualitative approach that started from the analytical and critical review of various bibliographic sources and academic positions from its beginnings to the present, taking into account authors such as Bostrom (2014), who developed a movement called "Social Transhumanism", inherited from the thought of Huxley (1957). Concluding that while it is true that transhumanism could have positive effects, developing more intelligent human beings, however, the dependence on technology makes it inaccessible to a large percentage of the population, with catastrophic effects for societies; therefore, the State must be the guarantor of these technological advances, it must ensure to educate and raise public awareness through ethical and legal regulations and controls, protecting human rights, eliminating discrimination to avoid inequalities and evaluating possible risks to citizens. Furthermore, transhumanism represents a great challenge to our understanding of the human, which is why it is essential to consider the ethical and social implications on the type of society we want to build in the near future.